What Sleeping Babies Hear - Graham, Alice M.; Fisher, Philip A.; Pfeifer, Jennifer H. (Psychological Science, 2013)
Experiences of adversity in the early years of life alter the developing brain. However, evidence documenting this relationship often focuses on severe stressors and relies on peripheral measures of neurobiological functioning during infancy. In the present study, we employed functional MRI during natural sleep to examine associations between a more moderate environmental stressor (nonphysical interparental conflict) and 6- to 12-month-old infants’ neural processing of emotional tone of voice. The primary question was whether interparental conflict experienced by infants is associated with neural responses to emotional tone of voice, particularly very angry speech. Results indicated that maternal report of higher interparental conflict was associated with infants’ greater neural responses to very angry relative to neutral speech across several brain regions implicated in emotion and stress reactivity and regulation (including rostral anterior cingulate cortex, caudate, thalamus, and hypothalamus). These findings suggest that even moderate environmental stress may be associated with brain functioning during infancy.